Analytical solution for temporal photorefractive response in the diffusion regime - Wichtowski, Marek; Weinert-Raczka, Ewa (Photonics Letters of Poland, 2009)
The evolution of a space-charge field during photorefractive two wave mixing in unbiased sample is considered. An approximate analytical solution describing the photorefractive material response to the interference pattern of arbitrary fringe contrast is presented. Obtained solutions are compared with the results of numerical simulations. Full Text: PDF References: J.P. Huignard, P. Gunter, "Photorefractive Materials and Their Applications I" (Springer-Verlag, Berlin, 1988) E. Serrano, M. Carrascosa, F. Agulló-López, "Analytical and numerical study of photorefractive kinetics at high modulation depths", JOSA B 13. 2587 (1996).[CrossRef] B.I.Sturman, E. F. Agulló-López, M. Carrascosa, L.Solymar, "On macroscopic description of photorefractive phenomena", Appl. Phys. B 68, 1013 (1999)[CrossRef] J.E. Millerd, E.M.Garmire, M.B. Klein, B.A.Wechsler, E.P.Strohkendl, G.A. Brost, "Photorefractive response at high modulation depths in Bi12TiO20", JOSA B 9, 1449 (1992)[CrossRef]